ANALYSIS OF THE SUITABILITY OF GRADE PARAMETERS, ANGLE OF TURN AND WIDTH OF PIT A MINE ROAD TO ENSURE THE SAFETY AND SECURITY OF THE MINE UNIT USING AERIAL PHOTOGRAPHIC DATA - Alawi, Ahmad Zaki; Setiaji, Wahyu Soleh (Journal of Marine-Earth Science and Technology, 2023)
One of the applications of survey science that exists in mining is aerial photo surveys. Data from aerial photo surveys can be used and utilized in various jobs, one of which is monitoring work including monitoring the safety of mining roads. Monitoring of mining roads aims to ensure the security and safety of workers in the process of mineral mining. In this study, the implementation of an aerial photo survey to provide an evaluation of the safety of mining roads based on the Decree of the Minister of Energy and Mineral Resources No. 1827 K/30/MEM/2018. The evaluation of the safety of mining roads is based on three parameters, namely road grade, road width, and road turn angle. Planning for the evaluation of the mine road was carried out through the data collection stage through an aerial photo survey on July 12, 2022, and data processing using Agisoft Metashape and ArcGIS. The output in data processing is in the form of a mine road safety map per parameter. Based on the results obtained in the classification of road grade values, a grouping was carried out with 4 classes, namely the very safe class, the safe class, the warning class, and the hazard class. For road grade parameters, 31% of mining roads at pit A site Alhasanie PT Equalindo are included in the dangerous category. In the width parameter of the mining road, 70% of the status is safe and has been in accordance with the Decree of the Minister of Energy and Mineral Resources No. 1827 K/30/MEM/2018. In the parameters of the turning angle of the mining road, 73% of the status is safe and has been in accordance with the Decree of the Minister of Energy and Mineral Resources No. 1827 K /30/MEM/2018.